CD8+ cytotoxic T cell responses to dominant tumor-associated antigens are profoundly weakened by aging yet subdominant responses retain functionality and expand in response to chemotherapy. (3rd April 2019) - Jackaman, Connie; Gardner, Joanne K.; Tomay, Federica; Spowart, Joshua; Crabb, Hannah; Dye, Danielle E.; Fox, Simon; Proksch, Stephen; Metharom, Pat; Dhaliwal, Satvinder S.; Nelson, Delia J.
ABSTRACT: Increasing life expectancy is associated with increased cancer incidence, yet the effect of cancer and anti-cancer treatment on elderly patients and their immune systems is not well understood. Declining T cell function with aging in response to infection and vaccination is well documented, however little is known about aged T cell responses to tumor antigens during cancer progression or how these responses are modulated by standard chemotherapy. We examined T cell responses to cancer in aged mice using AE17sOVA mesothelioma in which ovalbumin (OVA) becomes a 'spy' tumor antigen containing one dominant (SIINFEKL) and two subdominant (KVVRFDKL and NAIVFKGL) epitopes. Faster progressing tumors in elderly (22–24 months, cf. 60–70 human years) relative to young (2–3 months, human 15–18 years) mice were associated with increased pro-inflammatory cytokines and worsened cancer cachexia. Pentamer staining and an in-vivo cytotoxic T lymphocyte (CTL) assay showed that whilst elderly mice generated a greater number of CD8 + T cells recognizing all epitopes, they exhibited a profound loss of function in their ability to lyse targets expressing the dominant, but not subdominant, epitopes compared to young mice. Chemotherapy was less effective and more toxic in elderly mice however, similar to young mice, chemotherapy expanded CTLs recognizing at least one subdominant epitope in tumors and draining lymph nodes, yet treatment efficacy still required CD8 + T cells. Given the significant dysfunction associated with elderly CTLs recognizing dominant epitopes, our data suggest that responses to subdominant tumor epitopes may become important when elderly hosts with cancer are treated with chemotherapy.